The relationship among peak power output, lactate threshold, and short-distance cycling performance: Effects of incremental exercise test design - McNaughton, L. R.; Roberts, S.; Bentley, D. J. (The Journal of Strength and Conditioning Research, 2006)
The purpose of this study was to compare the physiological results of 2 incremental graded exercise tests (GXTs) and correlate these results with a short-distance laboratory cycle time trial (TT). Eleven men (age 25 ± 5 years, O2max 62 ± 8 ml·kg-1·min-1) randomly underwent 3 laboratory tests performed on a cycle ergometer. The first 2 tests consisted of a GXT consisting of either 3-minute (GXT3-min) or 5-minute (GXT5-min) workload increments. The third test involved 1 laboratory 30-minute TT. The peak power output, lactate threshold, onset of blood lactate accumulation, and maximum displacement threshold (Dmax) determined from each GXT was not significantly different and in agreement when measured from the GXT3-min or GXT5-min. Furthermore, similar correlation coefficients were found among the results of each GXT and average power output in the 30-minute cycling TT. Hence, the results of either GXT can be used to predict performance or for training prescription.